A Method to Estimate the Microstructures of Low‐Alloy Cold‐Rolled TRIP Steels. Issue 2 (24th October 2017) - Fu, Bo; Sun, Xiaoyang; Yang, Wangyue; Li, Longfei; Zhao, Zhenye
Abstract : A method is implemented in the present study to estimate the microstructures of low‐alloy cold‐rolled TRIP steels. This method includes simulations of intercritical annealing (IA) process and calculations of isothermal bainitic transformation (IBT) process. The evolutions of volume fractions and elements concentration profiles with temperatures and holding times for ferrite phase and austenite phase could be acquired assisted by Thermo‐Calc and DICTRA during IA process. Bainitic transformation from austenite, with chemical compositions determined at the end of IA, takes place during the subsequent IBT process. By taking into account the martensitic transformation during cooling from IA to IBT and/or from IBT to room temperature (RT) and avoiding the complex discussions of bainitic transformation kinetics, the volume fractions of bainite, martensite and retained austenite could be approximately determined after IBT and subsequent water quench. At the same time, the experimental validation of this method is conducted with well agreements. This implemented method is expected to relate chemical compositions and heat treatment parameters to the final microstructures of low‐alloy cold‐rolled TRIP steels and be beneficial for optimizing TRIP microstructures without amounts of experiments. Abstract : A simple method to predict the microstructures of cold‐rolled TRIP steels is founded. This method is based on simulations and calculations of two‐step heat treatment processes with Thermo‐Calc and DICTRA. Relationship between heat treatment parameters and final microstructures of TRIP steels are established through the method. Thus, optimization of microstructures for TRIP steels can be realized without amounts of experiments by using this method.